Defining student participation and empowerment in higher education - Boaventura, Patricia Silva Monteiro (2016)
Customer participation has been studied for decades; however, it gained a postmodern perspective around the year 2000. Customers have become co-creators of personalized experiences, moving from the audience to the stage. In the educational context, students must take responsibility for their learning process and participate in the production of the service. This changing is providing opportunities and challenges for higher education institutions (HEIs) to redefine their relationship with stakeholders, especially with students. This study is based on the service dominant logic (SDL) perspective because students are assumed to take the role of co-creators of knowledge in the educational setting. The research uses adapted frameworks and concepts applied in organizational, knowledge-intensive business services (KIBS) and also medical studies to advance the understanding of value co-creation in the HEI context. The current study addresses a lack of research in the higher education context focusing on defining students’ participation and students’ empowerment in higher education context. An empirical investigation was developed with traditional schools in Brazil. This investigation allowed the description of the constructs in the specific context. The description of student participation in HEIs context reflects the relevance of three dimensions – information sharing, personal interaction and responsible behavior. In the Brazilian context, responsible behavior is the weakest dimension in the construct, because the responsibilities are unbalanced between students and professors. The main reasons identified for this unbalanced relation were cultural issues and local regulation. Student empowerment was described as composed by four dimensions – meaningfulness, competence, impact and choice; however, one of them – choice – was identified as the weakest dimension, facing cultural and bureaucratic barriers for implementation in the Brazilian educational context. Moreover, interviewees spontaneously cited the idea of trust in the faculty as an important antecedent of student participation that must be considered when analyzing student participation and empowerment mechanisms. An additional contribution was the proposal of a theory-based framework for understanding the service dominant logic perspective in the HEI context, in which student participation and student empowerment were explored as mechanisms leading to positive student behavior toward institution.